Learning Design based on Educational Game Guessing Words: Increasing Concentration in Attention Deficit Hyperactivity Disorder Children - Masrum Masrum; Jasmin Haris; Hasan Baharun; Fathorrozi Fathorrozi; Sarofa Indrianti (Journal of Innovation in Educational and Cultural Research, 2023)
This paper aims to analyze and understand the increasing concentration of Attention Deficit Hyperactivity Disorder (ADHD) children through guessing games in Madrasahs. ADHD children have difficulty focusing, so learning while playing can be an alternative treatment. This research uses a qualitative case study approach. The data analysis technique is done through interviews, observation, and documentation. The data analysis uses Milles and Huberman's data reduction, data display, and drawing conclusions. The results showed that with the stages of forming groups as a mirror of the guidance process, then conveying game instructions as a form of persuasion, starting a guessing game as a form of accompanying, and having rewards as a form of response and more attention from the teacher then the final score of the game was obtained. It is being done, which continues to increase. It can then be understood that guessing games can improve concentration in ADHD children at Madrasah Ibdtidaiyah Misbahul Fata, Probolinggo. This study provides implications about the importance of learning design based on the needs of students that teachers must carry out by utilizing a multidisciplinary approach so that learning targets can be achieved.